Association of Interleukin-10 Polymorphism (rs1800896, rs1800871, and rs1800872) With Breast Cancer Risk: An Updated Meta-Analysis Based on Different Ethnic Groups - Li, Lijun; Xiong, Wei; Li, Donghua; Cao, Jiangang (Frontiers in Genetics, 2022)
Background: The interleukin10 (IL-10) gene polymorphisms have been indicated to be associated with breast cancer (BC) risk, but the findings are still controversial. To derive a more precise evaluation, we performed a comprehensive meta-analysis. Methods: A systematic literature search was conducted using PubMed, Embase, CNKI, China biomedical(CBM), and Google Scholar to March 29, 2020. Revman5.3 and Stata 12.0 software analyzed the data, and the strength of the association was identified using the odds ratio (OR) and the corresponding 95% confidence interval (CI). Results: A total of 23 studies (7250 cancer cases and 7675 case-free controls) were included in this meta-analysis. The results show that IL-10 gene polymorphisms were significantly correlated with BC risk based on subgroup analysis by ethnicity. The IL-10 rs1800896 polymorphism was significantly associated with the risk of BC in Asians (G vs. A: OR = 0.78, 95% CI = 0.65-0.95, P = 0.01; GG vs. AA: OR = 0.51, 95% CI = 0.31-0.84, P = 0.007; GA vs. AA: OR = 0.6, 95% CI = 0.44-0.81, P = 0.0009; GG+GA vs. AA: OR = 0.6, 95% CI = 0.45-0.81, P = 0.0007); Moreover, an increased BC risk in Asians were also associated with the IL-10 rs1800872 polymorphism (AA vs CC: OR = 0.74, 95%CI = 0.55-0.99, P = 0.04; A vs C: OR = 0.85, 95% CI = 0.74-0.98, P = 0.03). In addition, The IL-10 rs1800871 (CT vs. TT: OR = 1.8, 95% CI = 1.03-3.13, P = 0.04) and rs1800872 polymorphism (A vs C: OR= 0.65, 95% CI 0.43-0.98, P =0.04) were associated with BC risk in Caucasians. Conclusion: Collectively, this meta-analysis demonstrated that IL-10 rs1800896 and rs1800872 (AA vs CC; A vs C) polymorphisms significantly increased the risk of BC in Asians, while the rs1800871 and rs1800872 (A vs C) were associated with the risk of BC in Caucasians. Therefore, this may provide new ideas for predicting and diagnosing BC susceptibility through the detection of IL-10 gene polymorphism.